6-Chloro-4-(4-methylphenoxymethyl)-2H-chromen-2-one - Ramakrishna Gowda; K.V. Arjuna Gowda; Mahantesha Basanagouda; Manohar V. Kulkarni (Acta Crystallographica Section E, 2011)
In the title compound, C17H13ClO3, the coumarin and phenoxy moieties are essentially co-planar, making a dihedral angle of 1.99 (7)°. The phenoxy moiety is oriented antiperiplanar with respect to the coumarin ring as indicated by the C—C—O—C angle of −179.97 (16)°. In the crystal, the sheet-like packing is stabilized by intermolecular C—H...O and C—H...Cl hydrogen bonds.